2016
DOI: 10.1002/elan.201600572
|View full text |Cite
|
Sign up to set email alerts
|

Screen‐printed Tattoo Sensor towards the Non‐invasive Assessment of the Skin Barrier

Abstract: The development and characterisation of a screen‐printed tattoo sensor for the non‐invasive assessment of the skin barrier is presented. A screen‐printed silver tattoo sensor comprising two concentric circle electrodes was fabricated and applied and characterised initially on a soft tissue mimic. It was shown that the tattoo was capable of tracking changes in water content in the soft tissue mimic using impedance spectroscopy. The tattoo sensors were then applied to porcine and human skins and impedance spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…The lower frequency range can be attributed to the electrode-skin interface, and the higher frequency range to the skin itself. Figure 3d shows the impedance spectrum for human skin which formed a single semi-circle with a larger diameter to that of Labskin due to the high impedance of the SC in human skin as well as potentially the impedance given by the electrode-skin interface (i.e., due to lower level of conformal contact of the tattoo with human skin) [12]. It is interesting to note that in the human skin spectra, the diameter of the semi-circle is smaller for the male skin when compared to the female skin.…”
Section: Biophysical Properties and Temporary Tattoo Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower frequency range can be attributed to the electrode-skin interface, and the higher frequency range to the skin itself. Figure 3d shows the impedance spectrum for human skin which formed a single semi-circle with a larger diameter to that of Labskin due to the high impedance of the SC in human skin as well as potentially the impedance given by the electrode-skin interface (i.e., due to lower level of conformal contact of the tattoo with human skin) [12]. It is interesting to note that in the human skin spectra, the diameter of the semi-circle is smaller for the male skin when compared to the female skin.…”
Section: Biophysical Properties and Temporary Tattoo Sensorsmentioning
confidence: 99%
“…For example, Jia et al have demonstrated lactate sensing in sweat using a temporary tattoo amperometric sensing approach [10], and Bandodkar et al have demonstrated an enzyme based tattoo amperometric epidermal sensor for glycemic level monitoring during food consumption [11]. Our group has recently reported a screen-printed temporary tattoo sensor for non-invasive skin barrier assessment using impedance spectroscopy [12]. Impedance spectroscopy allows for non-invasive measurements of the overall resistance and reactance of skin using alternating current of various frequencies, where electrical impedance of intact skin is dominated by the SC at low frequencies (≤1 KHz) [13].…”
Section: Introductionmentioning
confidence: 99%
“…CPW lines have demonstrated higher sensitivity in dielectric properties extraction and material characterization compared to microstrip and slot lines [12,18,22,24,[29][30][31][32]. Normally, microstrip-based structures are used in resonance-based sensors due to the sensitivity of the microstrip gap.…”
Section: Sensor Designmentioning
confidence: 99%
“…Several sensors have been reported in literature that monitor electrolytes in sweat [11][12][13]. This includes using skin potentiometric sensors [11], impedimetric sensors [12], and multi-biomarker selective patches [13]. However, these devices require continuous contact with the skin during measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation